2018
DOI: 10.3390/urbansci2040115
|View full text |Cite
|
Sign up to set email alerts
|

Urban Intensities. The Urbanization of the Iberian Mediterranean Coast in the Light of Nighttime Satellite Images of the Earth

Abstract: The contribution shares the approach of critical urban studies that have conceptualized urbanization more as a process than as a sum of spatial forms. Thus, the contribution studies the urbanization process not only from the point of view of the physical occupation of land but also considers changes in the intensity of the uses of space. To fulfill this aim, the new sources of nocturnal satellite images are particularly useful. These allow us to observe the intensity of urban uses both in terms of their distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 21 publications
0
5
0
7
Order By: Relevance
“…En esta etapa de la investigación se tuvieron en cuenta como referencia los trabajos desarrollados por el Grupo de investigación sobre Energía, Territorio y Sociedad de la Universitat Autónoma de Barcelona (Nel.lo et al, 2016;Checa et al, 2017;Checa & Nel.lo, 2018).…”
Section: Tratamiento De La Informaciónunclassified
See 2 more Smart Citations
“…En esta etapa de la investigación se tuvieron en cuenta como referencia los trabajos desarrollados por el Grupo de investigación sobre Energía, Territorio y Sociedad de la Universitat Autónoma de Barcelona (Nel.lo et al, 2016;Checa et al, 2017;Checa & Nel.lo, 2018).…”
Section: Tratamiento De La Informaciónunclassified
“…Como el objetivo de la investigación gira en torno al conocimiento de la extensión de la superficie urbana a partir de la superficie iluminada y, como no todos los píxeles con valores mayores que cero corresponden a las áreas de cobertura urbana, se estimó un valor mínimo (intensidad lumínica) de referencia ligado a diversas construcciones materiales humanas (Checa & Nel.lo, 2018) 4 que en el presente trabajo se denominan de manera amplia infraestructura gris. Para concretar este paso, era necesario contar con una capa de cobertura urbana que permitiera realizar una superposicion sobre las imágenes nocturnas y poder aproximar un valor mínimo como umbral de luminosidad urbana.…”
Section: Tratamiento De La Informaciónunclassified
See 1 more Smart Citation
“…Jurgens et al, experimentally illustrated that there are not so many false location information [64]. Furthermore, recent studies have indicated that NTL data is highly correlated with urban infrastructures and socio-economic activities such as tourism [65,66]. Therefore, regions with either enough BF (or enough NTL intensity) are assumed to ensure minimum infrastructure necessary for tourism activities.…”
Section: Identifying Taois By Cluster Pruningmentioning
confidence: 99%
“…It has been extensively used in understanding the various anthropogenic phenomenon. Also, correlating the NTL brightness with other variables such as buildings and settlement areas, bridges and communication routes, and demographic and socio-economic activities have generated good results which have proved useful for decision making [65,66,82,83].…”
Section: Nighttime Lightmentioning
confidence: 99%